Dimethyl sulfoxide-κSbis[2′-(3-methyl-thiophen-2-ylmethylene) furan-2-carbohydrazido]zinc(II) - Ali, Hapipah Mohd; Yamin, B.M.; Yusof, M.S.M.; Omar, S.R.S. (International Union of Crystallography, 2003)
The title compound, [Zn(C12H10N2O 2S)2(C2H6OS)], is monomeric with the Zn atom in a five-coordinate environment. The geometry of the polyhedron is distorted trigonal bipyramidal, with angles of the equatorial atoms about the central Zn atom in the range 77.84 (10)-126.66 (12) Å. The O-Zn-O axial bond angle is 173.12 (12)°. © 2003 International Union of Crystallography Printed in Great Britain - all rights reserved.